2022
DOI: 10.1007/s41742-021-00387-1
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Potential of Common Disinfection Processes for the Removal of Virus from Wastewater

Abstract: Due to the prevalence of the COVID-19 outbreak, as well as findings of SARS-CoV-2 RNA in wastewater and the possibility of viral transmission through wastewater, disinfection is required. As a consequence, based on prior investigations, this work initially employed the viral concentration detection technique, followed by the RT-qPCR assay, as the foundation for identifying the SARS-CoV-2 virus in wastewater. After that, the ability and efficacy of chlorine, ozone, and UV disinfection to inactivate the SARS-CoV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 45 publications
(131 reference statements)
0
15
0
Order By: Relevance
“…Coronaviruses (CoVs) are responsible for three zoonotic epidemics in the last 20 years including severe acute respiratory syndrome (SARS) identified in China 2002–2003, Middle East Respiratory Syndrome (MERS) started in 2012 in the Middle East, and the current COVID-19 pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). As of December 2019, the first detection of COVID-19 was found in Wuhan, Hubei Province, China [4] , [5] , [6] . Then as of January 30, 2020, World Health Organization (WHO) declared the COVID-19 outbreak as a public health emergency of international concern [5] .…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Coronaviruses (CoVs) are responsible for three zoonotic epidemics in the last 20 years including severe acute respiratory syndrome (SARS) identified in China 2002–2003, Middle East Respiratory Syndrome (MERS) started in 2012 in the Middle East, and the current COVID-19 pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). As of December 2019, the first detection of COVID-19 was found in Wuhan, Hubei Province, China [4] , [5] , [6] . Then as of January 30, 2020, World Health Organization (WHO) declared the COVID-19 outbreak as a public health emergency of international concern [5] .…”
Section: Introductionmentioning
confidence: 99%
“…Findings indicated that both symptomatic and asymptomatic COVID-19 patients excreted SARS-CoV-2 virus through feces and other body secretions that disposed in wastewater. In the same vein, virus introduces into the wastewater treatment plants (WWTPs) by sewer systems [2] , [4] , [6] . Coronaviruses can survive for several days in wastewater under different situations and the plumbing systems are described as the possible transmission route for this kind of viruses in 2003 [2] , [4] , [5] , [7] .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations